ANALYSIS OF DETERMINING FACTORS OF TECHNOLOGY ADOPTION INTENTION IN COOPERATIVES IN DENPASAR CITY - Made Gita Saraswati; Surya Dewi Rustariyuni (INJOSEDU: International Journal of Social and Education, 2025)
Digital transformation is a crucial aspect in strengthening the competitiveness of cooperatives in the technology-based economy era. However, the rate of technology adoption among cooperatives in Denpasar City remains relatively low. This study aims to analyze the effects of performance expectancy, effort expectancy, social influence, and facilitating conditions on the intention to adopt mobile application technology in cooperatives in Denpasar City. A quantitative approach with an associative research design was employed. The study involved 85 active cooperatives that had not yet adopted technology, selected using purposive sampling. Multiple linear regression was used as the analytical method. The findings reveal that all four independent variables simultaneously have a significant effect on technology adoption intention. Partially, each variable also shows a positive and significant effect, with social influence identified as the most dominant factor. These findings contribute to the strengthening of the UTAUT theory and support the endogenous growth theory approach, which emphasizes the importance of institutional internal factors in driving innovation.